2008
DOI: 10.1097/ijg.0b013e31815f5345
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Changes After Intra-bleb Injection of Bevacizumab

Abstract: Subconjunctival injection of bevacizumab reduced bleb vascularity and may provide an adjunct to current antifibrosis therapy. Further studies to establish the effect of bevacizumab on postoperative scaring are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 6 publications
1
28
0
2
Order By: Relevance
“…Meanwhile, an increasing number of clinical case reports and observational case series described the potential beneficial effect of bevacizumab on glaucoma surgery outcome (Biteli and Prata, 2013;Coote et al, 2008;Kahook et al, 2006;Klos-Rola et al, 2013;Zarnowski and Tulidowicz-Bielak, 2011). A pilot study, performed with a small number of patients (12) to evaluate a single subconjunctival bevacizumab injection (1.25 mg; 50 ml), demonstrated that bevacizumab is a potential adjunctive treatment for reducing the incidence of bleb failure after trabeculectomy.…”
Section: Inhibition Of Vascular Endothelial Growth Factormentioning
confidence: 96%
“…Meanwhile, an increasing number of clinical case reports and observational case series described the potential beneficial effect of bevacizumab on glaucoma surgery outcome (Biteli and Prata, 2013;Coote et al, 2008;Kahook et al, 2006;Klos-Rola et al, 2013;Zarnowski and Tulidowicz-Bielak, 2011). A pilot study, performed with a small number of patients (12) to evaluate a single subconjunctival bevacizumab injection (1.25 mg; 50 ml), demonstrated that bevacizumab is a potential adjunctive treatment for reducing the incidence of bleb failure after trabeculectomy.…”
Section: Inhibition Of Vascular Endothelial Growth Factormentioning
confidence: 96%
“…Coote 23 reported the use of subconjunctival bevacizumab in a patient who exhibited bleb vascularity after uncomplicated clear corneal phacoemulsification cataract surgery. Three months prior to cataract surgery, the patient had undergone a limbal based trabeculectomy with Mitomycin C. Two weeks after the injection of bevacizumab, the bleb was noted to be significantly less vascular and by 6 months the bleb was quiet, diffuse, and functioning at an IOP of 10 mmHg.…”
Section: Post-operative Use Of Bevacizumabmentioning
confidence: 99%
“…M. Coote и J. Ruddle провели однократную инъекцию бевацизумаба в полость подушки на 10 дней после экстракции катарак-ты на глазах, перенёсших синустрабекулэктомию за 3 месяца до факоэмульсификации. В сроки до полугода они отмечали выраженное снижение степени васкуляризации ФП [11].…”
Section: применение ингибиторов Vegf после фистулизирующих антиглаукоunclassified